The Design and Synthesis of Novel 2, 3‐Dihydrobenzo[f]isoquinolin‐4(1H)‐ones via Sequential Ugi–Heck Reactions by Using an Efficient Heterogeneous Palladium Nanocatalyst. (15th December 2014) - Rasouli, Mohammad Ali; Miri, Simin; Rashidi Ranjbar, Parviz
Abstract : A facile and efficient synthesis of N ‐alkyl‐2‐(1, 2 dihydro‐1‐methylene‐4‐oxobenzo[f] isoquinoline‐3(4H)‐yl)‐2‐phenylacetamides is performed by the consecutive, two‐step procedure that consists of Ugi and Heck reactions. The Heck reaction was performed both by homogenous and a designed heterogeneous catalyst. The heterogeneous catalyst is a coordinated palladium to 1, 10‐phenanthroline attached to chitosan@Fe3O4 magnetite nanoparticles, which was shown to be more efficient than the homogenous Pd(OAc)2 /PPh3 catalyst with good to excellent yields. Abstract :